2007
DOI: 10.1002/chem.200700865
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)‐Mediated Aromatic ortho‐Hydroxylation: A Hybrid DFT and Ab Initio Exploration

Abstract: Mechanistic pathways for the aromatic hydroxylation by [CuII(L1)(TMAO)(O)](-) (L1=hippuric acid, TMAO=trimethylamine N-oxide), derived from the O--N bond homolysis of its [CuII(L1)(TMAO)2] precursor, were explored by using hybrid density functional theory (B3LYP) and highly correlated ab initio methods (QCISD and CCSD). Published experimental studies suggest that the catalytic reaction is triggered by a terminal copper-oxo species, and a detailed study of electronic structures, bonding, and energetics of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 117 publications
(200 reference statements)
1
25
0
1
Order By: Relevance
“…Thus, we consider C-H oxidation by a Cu(II)-oxyl ROS, dubbed the "oxyl mechanism" (Fig. 3) as this species has been previously predicted to exhibit a more strongly oxidative character than Cu(II)-superoxo (31,32 (20,33,34). From this system, we test two different geometries for oxidative attack at the C1 and C4 carbons to evaluate different enzyme-substrate poses (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we consider C-H oxidation by a Cu(II)-oxyl ROS, dubbed the "oxyl mechanism" (Fig. 3) as this species has been previously predicted to exhibit a more strongly oxidative character than Cu(II)-superoxo (31,32 (20,33,34). From this system, we test two different geometries for oxidative attack at the C1 and C4 carbons to evaluate different enzyme-substrate poses (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overall catalytic reaction and proposed mechanism for the hydroxylation of benzoate derivatives (TMAO is trimethylamine- N- oxide) (ref 121). …”
Section: Figurementioning
confidence: 99%
“…120,121 DFT calculations employed to analyze this process suggested that homolytic scission of the N–O bond in a copper(II) complex of trimethylamine- N -oxide (TMAO) yielded a copper(II)-oxyl intermediate. 121 A concerted pathway for hydroxylation of the aromatic ring by this intermediate was found to be favored relative to a stepwise hydrogen atom abstraction/rebound process. Copper(II)-oxyl species have also been proposed in other catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The species has not been observed in any molecular or enzymatic system, but indirect evidence has led several researchers to suggest such a species as a reactive intermediate. Several instances – experimental and theoretical – of intramolecular arene hydroxylation have been proposed to be promoted by a cupryl [58-60]. For example, oxygenation of a mononuclear Cu(I)-α-ketocarboxylate complex leads to intramolecular hydroxylation of a pyridyl phenyl arm (Figure 10) .…”
Section: Mononuclearmentioning
confidence: 99%